Landfill design based on methane gas emission estimates at Jatibarang Final Disposal Site (TPA) in Semarang City using LandGEM 3.03 and its potential utilization as an energy source - Sukma, Bayu; Kristanto, Gabriel Andari; Dahlan, Astryd Viandila (International Journal Labs, 2025)
This study aims to analyze the landfill design based on the estimated methane gas emissions at the Jatibarang Landfill, Semarang City, using the Landfill Gas Emissions Model (LandGEM) software version 3.03 and evaluate its potential utilization as an energy source. The study uses a quantitative approach utilizing mathematical modeling to estimate the estimated gas emissions from the landfill. The results show that the potential for electrical energy that can be generated from landfills is high enough to be recommended for management using the concept of Waste to Energy (WTE) into electrical energy. The recommendation that will be discussed is the management of methanogas emissions by being used as electrical energy, emphasizing infrastructure improvements for optimal energy production and reducing greenhouse gas emissions. This study could also incorporate real-time monitoring of gas emissions and energy production to better understand the dynamics of waste decomposition and the benefits of electricity generated from waste could foster community support for PLTSa initiatives.